Mechanical problem solving by plush-crested jays: are tools special after all? - Jimena Lois-Milevicich; Lauriane Rat-Fischer; María Alicia de la Colina; Raúl Orencio Gómez; Juan Carlos Reboreda; Alex Kacelnik (Animal Cognition)
Abstract Tool use is taxonomically associated with high behavioural flexibility and innovativeness, and its prevalence is greater in primates and some bird species. This association, however, is not known to be causally determinant of tool-related competence since flexibility and innovativeness are often observed in the absence of tool use and vice versa. For this reason, it is interesting to explore whether animals that can be loosely categorized as outstanding, or ‘intelligent’ physical problem solvers, are also remarkable using tools innovatively, rather than tool use presenting special constraints. We investigate this problem using plush-crested jays (Cyanocorax chrysops), a corvid new to cognitive research that shows highly flexible and inquisitive behaviour in the wild and has not been reported to use tools. We tested jays in two tasks of apparent similar manipulative complexity and incentive, one involving a tool (T) and the other not (NT). In the NT task birds had to open a box with a transparent lid blocked by a latch to get a reward, whereas in the T task, they had to use a rake to pull out the reward from the box. Eight out of nine subjects succeeded in the NT task, whereas none of them learned to solve the T task. This is consistent with tool use involving dedicated competencies, rather than just high problem-solving proficiency.